A review of problems and solutions of abandoned mines in South Africa. Issue 4 (3rd July 2016) - Mhlongo, Sphiwe Emmanuel; Amponsah-Dacosta, Francis
Abstract : Mining has been the backbone of the South African economy for many years. For over a century it has contributed considerably in the welfare of the people of South Africa. As a result of South Africa's long history of mining, the country has many abandoned mines that are currently the major source of various environmental and social problems. This review looks at the general problems of abandoned mines in South Africa and the efforts made towards rehabilitation of abandoned mine sites. The issues discussed include the controversy around the definition of abandoned mines, their associated problems, regulatory issues, prioritisation of rehabilitation and the rehabilitation cost estimation concerns. It was concluded that in order to fast track the work of cleaning up the negative legacy of abandoned mines in South Africa, appropriate definition for these mines should be identified and used in guiding the work of developing the country's abandoned mines inventory while assisting in the prioritisation of rehabilitation efforts. The abandoned mines rating system and the cost estimation model that can account for the site-specific issues in the rehabilitation of abandoned mines were recommended.